Does Recent Regulation Improve (or not) the Spanish Mutual Guarantee System? - Cardone-Riportella, Clara; GarcÃa-Mandaloniz, Marta (International Journal of Economics and Financial Issues, 2017)
This paper aims to analyse the new regulation framework and its impact on the Spanish mutual guarantee system (MGS), especially on the cost of the guarantee. The main conclusions are that the reforms which were introduced do not directly affect the reduction of this guarantee cost. Nevertheless, in our opinion, the regulation has strengthened the mutual guarantee system during the crisis as a result of the banks generating confidence to this financial intermediary, which helps to correct credit market failures. Currently, banks are more likely to recognize the role of the MGS and the declining risk involved thanks to the guarantee offered by the MGS that exhibits stronger solvency, liquidity and good governance policies. Keywords: small business regulation, mutual guarantee system, guarantee cost. JEL Classifications: D82, G21, G30